PSIV-15 Interaction between E+ and Abr loci is associated with brindle coat color in Korean Hanwoo cattle. (7th December 2018) - Park, M; Lee, S; Park, B; Lee, S; Choy, Y; Choi, J; Lee, K; Dang, C; Chang, H; Choi, Y; Kim, S
Abstract: Hanwoo ( Bos taurus coreanae ), an indigenous cattle breed of Korea, has three distinct coat color namely brown, brindle and black. Brindle or tiger-striped is an intermingled color between black and red or yellow. The brindle pattern is expressed by the interactions between two genes where the presence of a wild-type E + allele in one locus (E) is essential and its distribution on the body parts depends on the effects of alleles at other loci. This study aims to know the genetic basis of brindle coat color in Korean Hanwoo cattle population. PCR-RFLP pattern showed that the majority of the animals (97.46 to 98.91% of the brindle Hanwoo cattle) genotyped for MC1R and ASIP genes harbored E + E + and E + e, and A br A br and A br A alleles, respectively. The reconstructed haplotypes between MC1R and ASIP genotypes showed that the epistatic interactions between E + and A br alleles were responsible for brindle coat color expression (Table 1). Therefore, the haplotypes E + E + A br A br, E + E + A br A, E + eA br A br and E + eA br A expressed predominantly brindle phenotype those included 96.38% of the studied brindle population. As expected, the haplotypes E + E + AA and E + eAA were mostly associated with black or black derived coat colors in Hanwoo due to the dominant effects of wild type E + allele (E locus) over the hypostatic agouti allele (A locus). Besides, e allele could only be expressed in the absence of E + allele in the haplotypes and therefore, the resultant haplotypes eeA br A br, eeA br A and eeAA produced brown colored Hanwoo. Notably, the interactions between A and heterozygote E loci (E + eA br A br and E + eA br A) produced relatively higher proportion of brown cattle which also depicted the essential role of homozygote E + allele for complete expression of brindle pattern. Taken together, the brindle coat color inheritance in Hanwoo cattle has established through this study and are also supported by the previous findings in cattle.